Bibliometric Analysis of Compliance and Completeness in Electronic Medical Record Filling: Trends and Insights from Hospital Documentation - Endang Suprihati Ningsih; Herawati Herawati; Silvia Kristanti Tri Febriana; Edi Hartoyo; Ardik Lahdimawan (Universitas Malahayati Lampung, 2024)
ABSTRACT The introduction of Electronic Medical Records (EMR) has revolutionized healthcare documentation, emphasizing the importance of compliance and completeness in medical data recording. This study aims to analyze the bibliometric data and visualize the publication trends related to compliance and completeness in EMR using VOSviewer. We employed a bibliometric approach to identify key clusters and relationships among terms in the literature from various journals and countries over recent years. The results highlight three main clusters: documentation and adherence, data completeness and quality, and accuracy and compliance in hospital settings. The analysis shows a significant global interest, with the USA, Germany, and Indonesia being major contributors. The study also reveals a rise in publications from 2018 to 2022, predominantly consisting of research articles. The most cited article,